Serodiagnosis of toxocariasis by ELISA Test in handlers of dogs and cats in Karbala city, Iraq - AL.Daamy, BAF; Al-khaled, MJA (Journal of the Hellenic Veterinary Medical Society, 2025)
Human toxocariasis is one of the most widespread parasitic infections in the world and more common in poor and tropical nations. Ingesting the eggs shed on the faces of the specific dog or cat host infection results in infection of humans. Although toxocariasis in humans can cause a variety of clinical symptoms, the two most commonly reported clinical symptoms are visceral and ocular larval migration. The quantity and migration routes of Toxocara larvae determine the majority of the clinical symptoms and consequences associated with infection with this parasite. The gold standard for diagnosing Toxocariasis in humans is the visual identification of larvae in tissues and organs; the reference test for immunodiagnosis is an enzyme-linked immunosorbent assay that detects immunoglobulin-G antibodies against the excretory-secretory antigen of Toxocara. The current investigation was carried out from July to October 2023 in order to first determine the seroprevalence of Toxocariasis in the population of Karbala City and to document its association with a few epidemiological parameters. An enzyme-linked immunosorbent test (ELISA) approach was used in the human investigation. The study analyzed 50 blood samples from dog and cat handlers using an enzyme-linked immunosorbent assay (ELISA). The total seroprevalence of Toxocariasis was 9 (18%). The results showed that 5 (20%) more cat owners than dog owners had the infection, compared to 4 (16%) cat owners. The infection is more common in male handlers (23%), compared to female handlers (12.5%), with the maximal seroprevalence (44.4%) found in the age range of 5 to 15 years. In comparison to urban areas (8.6%), toxocariasis is more common in rural areas (25.9%). The association between sex and lifestyle and the incidence of Toxocariasis in humans was not statistically different (p > 0.05) while significant with age . The importance of this study was about investigating and proving the presence of the infection in Iraq, especially in Karbala Governorate, since most of the infections are without signs at the beginning of the infection, in addition to showing the importance of dealing carefully with domestic animals, which may be a source of transmission of the infection to breeders. The study also indicated that the infection risk rate is equal for genders and lifestyle, and the possibility of infection is the same for those who live in the countryside or the city.